Early Exploratory Intervention in Scrotal Trauma. Issue 2 (April 2013) - Bocchi, Francesca; Benecchi, Luigi; Russo, Fabrizio; Perucchini, Laura; Bocchi, Pietro; Martinotti, Mario; Del Boca, Carlo
Introduction: The aim of our study is to assess the incidence of the surgical approach in scrotal trauma. Materials and Methods: We retrospectively assessed both penetrating and blunt cases of scrotal trauma observed from 2002 to 2012. For each case we considered various parameters such as the age of the patient, whether the type of trauma was penetrating or blunt, whether or not a surgical approach was taken, whether or not there were polytrauma, whether or not an orchiectomy was performed, and how many days had elapsed since the first urological observation of the trauma. Results: 43 cases of scrotal trauma were assessed, of which 39 were blunt traumas (90%) and four penetrating traumas (10%). The median age of all patients was 29 years (range 4–88). Of these patients, eight underwent surgical procedures, of which three were cases of penetrating scrotal trauma and five were cases of blunt trauma, with an average age of 20. We only found it necessary to carry out an orchiectomy in two of these patients, of which one was after penetrating trauma and the other after blunt trauma. Most of the blunt traumas did not require surgery (8 versus 35, p<0.05). Conclusions: In our case studies, in the majority of cases early exploratory intervention in scrotal trauma allows the testicle to be saved in its entirety or at least in part.